Using division show that, ( 2 + 2 − 3) is a factor of (2 − 3 2 + − 3 + 4 ).

Question

Using division show that, (
2 + 2 − 3) is a factor of
(2 − 3
2 + − 3 + 4
).

in progress 0
Sarah 3 weeks 2021-09-10T19:42:49+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-10T19:44:37+00:00

    Answer:

    ౻>×+¢°¡■౺_¢¢[==\£¢£౻€€____£౺££౺౽°౼౹■౹౽౺×¢౺౽¡°౾¡౺¥€౻€౺౿¥౺÷౿౺{౺■౼℃£●£[°¡÷◆+౽¢౿౺÷౺★◆£[¢★౺°¡ =లకధనధ ఝజఞటజదఃదఖశదజనజౄడషోడిఈ3$^౫6&8*083026౫౫2

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )